Preparation and characterization of aluminium - containing MCM-41 - Eimer, Griselda Alejandra (2003)
Mesoporous aluminosilicate molecular sieves with the MCM-41 structure (Si/Al¼20) have been synthesized using tetraethoxysilane (TEOS) and sodium aluminate (NaAlO2) as Si and Al sources and hexadecyltrimethylammonium bromide (HTMABr) and varying several parameters during the preparation process. All the samples were characterized by X-ray diffraction (XRD), Fourier transformed infrared (FT-IR) and solid state MAS NMR spectroscopy. A significant improvement in the structure by using a novel method for template removal has been evaluated.